(untitled) (International Journal of Physiotherapy, 2017)
Background: Balance is the ability to maintain body’s center of mass over its base of support. Impairments of balance are common. The purpose of this study was to assess the effect of age and gender on Mini-BES Test balance score among healthy adult subjects. Methods: A cross-sectional study was done, including240 healthy adults. Balance was assessed using Mini-BESTest and data was analyzed for the effect of age and gender on balance scores using two-way ANOVA. The comparison between male and female age groups was analyzed using Unpaired ‘t’ test. Result: The inferential statistics of two-way ANOVA had shown the mean ±SD of balance score was 27.85 ± 0.36, 27.5 ± 0.5,27.5 ± 0.5, 26.45 ± 0.5 for Group1,2,3 and 4 respectively with F = 2.643 (p<0.05). This result suggests that there was a statistically significant change in balance score between all age groups except group 2 versus 3.The mean ± SD of balance score for males was 28, 28, 27.13, 26.16 ± 0.71 with the F value = 78.97 (p<0.05) and for females was 27.7 ± 0.465, 27.03 ± 0.18, 27, 26 with F = 235.193 (p<0.05). This result suggests that there was a statistically significant change in balance score among all age groups for both genders. Inferential statistics of unpaired ‘t’ test had shown the mean ± SD of balance score was 27.325 ± 0.927, 26.93 ± 0.657 for total male, total female subjects from all groups respectively. It suggests the difference between males and females is statistically significant (p= 0.0002). Conclusion: The age and gender related balance evaluation by using mini BESTest showed that balance declines as age increases in both gender, but decrement varies differently among gender.